2009
DOI: 10.1111/j.1526-4610.2009.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate Treatment of Chronic Migraine: A Randomized, Placebo‐Controlled Trial of Quality of Life and Other Efficacy Measures

Abstract: In addition to significantly reducing mean monthly migraine/migrainous and migraine headache days, treatment of chronic migraine with topiramate was effective with regard to several traditionally important and clinically relevant secondary outcomes in migraine prevention trials. Treatment with topiramate was well tolerated and not associated with serious adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 37 publications
3
76
0
4
Order By: Relevance
“…Double-blind, placebo-controlled, randomized, and parallel-group studies evaluating patients with chronic migraine who excessively used analgesics showed that topiramate in relatively low doses (50 to 100 mg/day) reduced the frequency of days with pain 71,74 and improved the quality of life of these patients 79 . This action was more efficient after the first four weeks of drug use 79 .…”
Section: Topiramatementioning
confidence: 99%
“…Double-blind, placebo-controlled, randomized, and parallel-group studies evaluating patients with chronic migraine who excessively used analgesics showed that topiramate in relatively low doses (50 to 100 mg/day) reduced the frequency of days with pain 71,74 and improved the quality of life of these patients 79 . This action was more efficient after the first four weeks of drug use 79 .…”
Section: Topiramatementioning
confidence: 99%
“…In a large double-blinded placebo-controlled multicenter study, topiramate, while failing to meet its primary endpoints of a decrease in mean monthly total headache days and headache-free days, demonstrated efficacy on several secondary efficacy measures. 71 These included significant reduction of migraine/migrainous days, total headache days, and headache-free days, and improvement in quality of life scores. The mean reduction of monthly headache days was 5.8 for topiramate vs 4.7 days for placebo.…”
Section: Topiramatementioning
confidence: 98%
“…There are plenty of studies on the effect of therapeutic or prophylactic management of the migraine on HRQOL. In a study in the USA, the effect of treatment with topiramate as the prophylactic treatment of migraine on QOL showed significant improvement of the QOL in the treatment group compared to the control group (13). In another study, the effect of the treatment with propranolol versus behavioral management was assessed; combination of propranolol and behavioral man-agement had positive effect on the QOL (14).…”
Section: Introductionmentioning
confidence: 99%